2012
DOI: 10.5194/cpd-8-5209-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial gradients of temperature, accumulation and δ<sup>18</sup>O-ice in Greenland over a series of Dansgaard-Oeschger events

Abstract: Air and water stable isotope measurements from three Greenland deep ice cores (GISP2, NGRIP and NEEM) are investigated over a series of Dansgaard-Oeschger events (DO 8-9-10) which are representative of glacial millennial scale variability. Combined with firn modeling, air isotope data allow to quantify abrupt temperature increases for each drill site. Our data show that the magnitude of stadial-interstadial temperature increase is up to 3 °C larger in Central and North Greenland than in North West G… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 105 publications
6
23
0
Order By: Relevance
“…Palaeoclimate fluctuations between colder and warmer periods representing glacial millennial scale variability have been reported for the NEEM and other Greenland cores (Guillevic et al 2012;NEEM Community Members 2013). Here, the two deep clathrated ice samples (1729.75 and 2051.5 m) provide a good example of contrasting deposition climates and correspondingly a one order of magnitude microbial cell abundance difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palaeoclimate fluctuations between colder and warmer periods representing glacial millennial scale variability have been reported for the NEEM and other Greenland cores (Guillevic et al 2012;NEEM Community Members 2013). Here, the two deep clathrated ice samples (1729.75 and 2051.5 m) provide a good example of contrasting deposition climates and correspondingly a one order of magnitude microbial cell abundance difference.…”
Section: Discussionmentioning
confidence: 99%
“…For all cores, the outer surface layer before decontamination contained one to two orders of magnitude higher cell numbers (not presented). As shown in Table 1, ice from 1729.75 m depth had the highest cell numbers, which corresponded to high Ca 2 ' and dust concentrations and as expected was deposited during a colder climate (Guillevic et al 2012). …”
Section: Microbial Abundancementioning
confidence: 99%
“…The modelling approach used here is identical to the one used to derive the NEEM gas chronology . Firn densification physics is described by a dynamical version of the HerroneLangway model (Herron and Langway, 1980) with ice Guillevic et al (2013) (GI-9)). d) Empirical Dage constraints for GISP2 (green dots) and GRIP (magenta squares) are superimposed onto the modelled Dage curves with uncertainty envelope for GISP2 (black, green) and GRIP (red, pale red).…”
Section: Gisp2 Gas Chronologymentioning
confidence: 99%
“…Furthermore, the reference horizons can provide ages and serve as ground truth when tracking radar layers on radio echograms between ice-coring sites (Karlsson et al, 2013;Panton, 2014) and the horizons can potentially constrain models describing the past conditions of the Greenland Ice Sheet (GIS). Finally, a consistent chronological framework for the network of Greenland deep ice cores allows an estimation of past elevation changes of the ice sheet NEEM Community Members, 2013) and gives insight into past regional climate variability and dynamics in much greater detail than previously attained (Langen and Vinther, 2009;Guillevic et al, 2013;Buizert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies combining air isotopic measurements (δ 15 N of N 2 ) with firnification models have suggested that, both in NGRIP and NEEM, the accumulation rates reconstructed from the GICC05 or ss09sea chronologies, through layer counting and the DJ flow model, were overestimated for the last glacial period (Huber et al, 2006;Guillevic et al, 2013;Kindler et al, 2014). Indeed, δ 15 N of N 2 of air trapped in an ice core indicates the depth and the amplitude of abrupt temperature changes in the gas phase through thermal fractionation.…”
Section: B Lemieux-dudon Et Al: Datice: Duration Constraintsmentioning
confidence: 99%